A Survey of Player-based and Link-based Allocation Rules for Network Games. (June 2014) - Borkotokey, Surajit; Gogoi, Loyimee; Sarangi, Sudipta
In this survey, we present recent developments in the literature on Network games. We briefly cover the literature on Communication situations and the corresponding allocation rules. This is followed by a review on the existing player- and link-based fixed and flexible allocation rules for networks. It is worth mentioning that all the allocation rules hitherto found in the literature are either player- or link-based which means that they give emphasis either on the players or on the links they form, but not both equally.